Interaction between RNA polymerase and a ribosomal RNA promoter of E. coli. - Hamming, J (1979)
The interaction between RNA polymerase and the E. coli ribosomal (r) RNA promoter(s) of the rrnE operon has been studied by the filter-binding method. The extent of complex formation between RNA polymerase and rrnE promoter(s) is salt-dependent; ppGpp specifically inhibits interaction of RNA polymerase with the rrnE promoter(s). A tentative model is proposed for the molecular events in the early steps of rRNA initiation: a transition of the primarily formed, labile RNA polymerase-rRNA promoter complex to a more stable form is the determining step. This step is salt-sensitive; ppGpp acts on this "isomerization".